Structura 2 : the art of sparth. - Bouvier, Nicolas, 1929-1998; Robertson, Scott, 1966- (Culver City : Designstudio, 2011)
This visually stunning book includes never-before-seen art from video game concept artist Sparth. As well as images from Assassin's Creed and Halo, he also showcases his book cover art, as well as fantasy and science fiction pieces. His work is accompanied by step-by-step tutorials on different Photoshop techniques. This is an unmissable volume for fans of Sparth's work and aspiring designers.